Prospecting aquifers with electromagnetic methods in the city of Ávila, Spain - Zevallos Flores, Arturo Santos (2020)
The municipality of Casas del Puerto is located SW of the city of Ávila, currently it does not have enough water for human consumption and irrigation, so groundwater represents a great possibility of having the water resource, for which a method Very Low Frequency VLF Electromagnetic. Profile length measurements should be long enough, at least to encompass the total anomaly. The article aims to determine the hydrogeological possibilities of the materials that make up the research area in the Municipality of Casas del Puerto, Ciudad de Ávila, which has plots (1-18-31), polygons (3-4- 6), with a total area of 10,844 hectares, likewise determine the conductivity of the bodies, to later characterize it lithologically and hydrogeologically and finally determine the most favorable areas to place groundwater collection wells. With the geological Interpretation and an analysis of the real Component (angle of inclination) and imaginary (ellipticity), it was possible to differentiate two zones with less hydrogeological possibility, therefore Zone-3 presents a great contrast of the conductive bodies, due to the contact area.